1997
DOI: 10.1143/jjap.36.3864
|View full text |Cite
|
Sign up to set email alerts
|

Local Tunneling Barrier Height Imaging on Si(111) Surface

Abstract: The present paper describes a three-dimensional (3D) thick-photoresist microstructuring technique that exploits the effect of exposure wavelength on dissolution rate distributions in a thick-film diazonaphthoquinone (DNQ) photoresist. In fabricating 3D microstructure with specific applications, it is important to control the spatial dissolution rate distribution in the photoresist layer, since the lithographic performance for 3D microstructuring is largely determined by the details of the dissolution property.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The work function on well-defined single-crystal surfaces has been widely reported for Si, [6][7][8] TiO 2 , 3,4,11,13,15,26,27 Au, 9 Pt, 10,12 and so forth. In general, the crystal face dependence in the work function was explained by the electric double layer formed by the asymmetric distribution of electric charges which depends on the crystal faces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work function on well-defined single-crystal surfaces has been widely reported for Si, [6][7][8] TiO 2 , 3,4,11,13,15,26,27 Au, 9 Pt, 10,12 and so forth. In general, the crystal face dependence in the work function was explained by the electric double layer formed by the asymmetric distribution of electric charges which depends on the crystal faces.…”
Section: Discussionmentioning
confidence: 99%
“…The work function of the semiconductor surface has been investigated by using a variety of surface science techniques, including a Kelvin probe force microscope (KPFM), a scanning tunnel microscope (STM), and ultraviolet photoelectron spectroscopy (UPS). Especially the STM and KPFM techniques provide information of the local work function with the spatial resolution of a few nanometers. Sasahara et al investigated the local work function of atomic-level regulated TiO 2 (110) surfaces, prepared by the Ar + ion sputtering and thermal annealing under UHV conditions, with a lateral resolution of several nanometers by using KPFM. , Crystalline islands on an extended terrace exhibited higher work functions than the terrace itself. , The increment of the work function was dependent on the size of the islands; a small island presented an enhanced increment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local barrier height (LBH) measurement using STM enables us to estimate the local work function of metal [28,29] and semiconductor [30][31][32] surfaces. Several research groups have applied LBH measurement to alkali metals [33][34][35] and oxygen atoms [36,37] deposited on semiconductor surfaces, and found that charge transfer occurred between the adsorbates and substrates.…”
Section: Scanning Tunneling Microscopymentioning
confidence: 99%
“…φ = 0.952 (d ln I/ds) 2 [4]. A number of authors have presented such "local barrier-height" (LBH) or "local work-function" images of surfaces (that is, local variations of φ) as an alternative to the more commonly shown "topographic images" [5][6][7][8]. In this LBH mode of imaging, the tip-to-sample gap distance is modulated at a frequency above the feedback loop cutoff, such that the mean distance, which is the mean value of the tunneling current, is constant.…”
mentioning
confidence: 99%